Radiation Therapy in Extensive Stage Small Cell Lung Cancer - Jeremic, Branislav; Gomez-Caamano, Antonio; Dubinsky, Pavol; Cihoric, Nikola; Casas, Franesc; Filipovic, Nenad (Frontiers in Oncology, 2017)
Lung cancer is the major cancer killer in the Western world, with the small cell lung cancer (SCLC) representing around 15-20% of all lung cancers. Extensive disease small cell lung cancer (ED SCLC) is found in approximately two-thirds of all cases, composed of both metastatic (M1) and nonmetastatic (but presumably with tumour burden too large for locoregional-only approach) variant. Standard treatment options involves chemotherapy (CHT) over the past several decades. Radiation therapy (RT) had mostly been used in palliation of locoregional and/or metastatic disease. In contrast to its established role in treating metastatic disease, thoracic RT (TRT) had never been established as important part of the treatment aspects in this setting. In the past two decades thoracic oncologists have witnessed wide introduction of modern RT and CHT aspects in ED SCLC which led to more frequent use of RT and rise in the number of clinical studies. Since the pivotal study of Jeremic et al, who were the first to show importance of TRT in ED SCLC, a number of single-institutional studies have reconfirmed this observation, while recent prospective randomized trials (CREST and RTOG 0937) brought more substance to this issue. Similarly, the issue of prophylactic cranial irradiation (PCI) was investigated in EORTC and the Japanese study, respectively, bringing somewhat conflicting results and calling for additional research in this setting. Future studies in ED SCLC could incorporate questions of RT dose and fractionation as well as the number of CHT cycles and type of combined Rt-CHT (sequential vs concurrent).